Statistics : informed decisions using data - Sullivan, Michael III , 1967- (Pearson, 2013)
Accompanying CD-ROM contains Applets; Additional Topics; Formula Card; DDXL the Excel add-in; Data sets in Excel, JMP; MINITAB; SPSS; TI-83/84 plus; and TXT format